Penentu utama permintaan pelancong antarabangsa ke Malaysia dari pasaran Asia Timur dan Pasifik - Othman, Redzuan; Mohd Salleh, Norlida Hanim (Universiti Utara Malaysia, 2006)
In the last two decades the Malaysian tourism industry had witnessed a tremendous growth. Between 1985 to 2002, international tourist arrivals and revenue generated from tourism had increased from 3.1 million respectively. East Asia and the Pacific market have shown a tremendaous growth in international tourist arrivals as compared to other major tourist destinations. According to the World Tourist Organisation(WTO) the share of international tourist arrivals from this market had increased impressively within the last 5 decades. In 1960, this destination controlled less than 1% of the total international tourist arivals globally but by the year 2010 this market is expected to increase its control to nearly 20% which is more than the share of the Americas market. Malaysia is on of the destinatins of this market. More interestingly, a major group of international tourist arrivals to Malaysia is coming from this area. The increased in international tourist was due to the various pull and push factors. This study tries to determine and estimate the importance of various economic factors that might affect their traveling decision to this country. Among other important economic factors identified are costs of travelling in Malaysia, tourist income, foreign exchange rates, promotional activites, economic downturn and natural disasters such as the incidence of haze and international political instability. Employing a conventional demand model,this study is trying to estimate empirically the importance of these economic variables. Overall, research findings are consistent with theoretical framework and econometrics approach.More than half of the variables in this study are important in influencing the international tourist arrivals to this country. The elasticity of price (cost of traveling) is relatively more elastic than other elasticities.